Pencegahan dan Penanganan Perilaku Agresif Remaja Melalui Pengelolaan Amarah (Anger Management) - Laela Siddiqah (Jurnal Psikologi, 2010)
This study examined the effectivity of the anger management program for reducing aggression in risk‘s adolescents. Through the cognitive‐behavioral approach, the program was designed to process the cognitive, affective, and behavior aspects together for managing anger and facing the provocative situation without aggression. Fourteen participants in experimental group following eigth sessions of anger management program in 4 weeks, and 14 participants in control group do not obtain any treatment. The measurement of aggression to be held before the program start and a week after the program end. With the Anava Mixed Design, the result show that the anger management program have a significant effect in the changes of the participant’s aggression [F(1,22)=6.300, p<0.05, η 2 =0.06]. The changes of aggression in experimental group prove that the anger management program has practical meaningfull and useful for reduce the aggression in youth. In the other hand, the higher aggression at post‐test in control group prove that the aggression will be increased if there was no treatment for the adolescents with the high‐rate of anger. Future studies with larger samples may be able to detect the significant contributions of the anger management program for reducing aggressive behavior in youth.